Testing The Resilience of Sharia Bank During Covid-19 Pandemic - Nefo Indra Nizar; Ivan Putranto; Ahmad Yani Nasution (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
The purpose of this study was to test the resilience of Islamic banks in Indonesia facing Covid-19 which has not shown humility. The resilience of financial institutions, including Islamic banks, is needed so that the stability of financial institutions can be maintained. Several macroprudential policies have been implemented. The research method uses quantitative methods with the Primary Component Analysis technique. The research model refers to the theory of economic evolution. There are stages of bank resilience, starting from the normal stage, persistence and adaptability. The data used was secondary data with data sources from the OJK for performance indicators of Islamic banks with a total of twenty provinces in Indonesia. Data related to the covid-19 pandemic uses data from covid19.go.id. Based on the results of the study, there was a decrease in bank resilience due to Covid-19 pandemic. West Java Province is the province with the highest relative bank resilience score compared to other provinces, with a resilience score of 6.35. Meanwhile, from the results of the KMO test and Bartlet's Test the research data is feasible to use with the KMO value of each normal scenario, persistence and adaptability are greater than 0.05 and Bartlet's Test is significantly (sig = 0.000).